2007
DOI: 10.1017/s0142716407070257
|View full text |Cite
|
Sign up to set email alerts
|

The development of phonetic representation in bilingual and monolingual infants

Abstract: The development of native language phonetic representations in bilingual infants was compared to that of monolingual infants. Infants (ages 6–8, 10–12, and 14–20 months) from English–French or English-only environments were tested on their ability to discriminate a French and an English voice onset time distinction. Although 6- to 8-month-olds responded similarly irrespective of language environment, by 10–12 months both groups of infants displayed language-specific perceptual abilities: the monolinguals demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
154
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(169 citation statements)
references
References 57 publications
(79 reference statements)
13
154
1
1
Order By: Relevance
“…Later on, in the second half of their first year, infants show changes in phonetic discrimination following exposure to the native language(s) (Werker & Tees, 1984). In the case of monolingual exposure, children demonstrate realignment to the phonetic boundaries of one language; in bilingual situations, language-specific perceptual abilities develop in two languages, at least for highly frequent phones (Burns, Yoshida, Hill, & Werker, 2007;Sundara, Polka, & Molnar, 2008). When it comes to learning regularities in the input, preverbal 12-month-old bilingual infants, as opposed to monolinguals, show no problem learning multiple speech structures at the same time (Kovacs & Mehler, 2009b).…”
Section: Building Multiple Language Representations In Infant Trilingmentioning
confidence: 99%
“…Later on, in the second half of their first year, infants show changes in phonetic discrimination following exposure to the native language(s) (Werker & Tees, 1984). In the case of monolingual exposure, children demonstrate realignment to the phonetic boundaries of one language; in bilingual situations, language-specific perceptual abilities develop in two languages, at least for highly frequent phones (Burns, Yoshida, Hill, & Werker, 2007;Sundara, Polka, & Molnar, 2008). When it comes to learning regularities in the input, preverbal 12-month-old bilingual infants, as opposed to monolinguals, show no problem learning multiple speech structures at the same time (Kovacs & Mehler, 2009b).…”
Section: Building Multiple Language Representations In Infant Trilingmentioning
confidence: 99%
“…Une tendance similaire chez des enfants bilingues d'autres langues a été également observée dans un travail récent publié par Werker et collaborateurs (Burns et al, 2002). Dans une série d'expériences, ils ont examiné le décours du développement et la nature de représentations phonétiques relatives aux frontières catégorielles entre [b], [p] et [ph].…”
Section: La Discrimination Des Langues Par Le Bébé En Environnement Bunclassified
“…This view does not include stages of language unification but instead, distinctive linguistic systems from the onset of acquisition (Paradis, Genesee, & Crago, 2011). It hypothesizes that from infancy, there is a comprehensive ability to distinguish phonological systems from each language found in their environment from ages 10-12 months (Burns, Yoshida, Hill, & Werker, 2007). It expects expressive production to reflect an understanding of the separation of languages, including separate grammatical systems and lexicon.…”
Section: Language Acquisition and Bilingualismmentioning
confidence: 99%
“…The Dual Language System Hypothesis has gained the most support from recent research on speech perception, phonology, vocabulary, and morphosyntax (Paradis, et al 2011). Burns, Yoshida, Hill and Werker (2007) found that infants, 10-12 months of age, had the perceptual capacity to detect slight language-specific phonological differences between [p] and [b] production of English and French. Paradis (2001) tested the phonological production of English-French in 18-month old bilinguals.…”
Section: Language Acquisition and Bilingualismmentioning
confidence: 99%